What Works in Conservation 2015 - Nancy Ockendon
This book provides an assessment of the effectiveness of 648 conservation interventions based on summarized scientific evidence. Chapters cover the practical global conservation of amphibians, bats and birds, conservation of European farmland biodiversity and some aspects of enhancing natural pest control, enhancing soil fertility and control of freshwater invasives. It contains key results from the summarized evidence for each conservation intervention and an assessment of the effectiveness of each by international expert panels. The accompanying website www.conservationevidence.com describes each of the studies individually and provides full references.